A Study of Holders Inequality in New Spaces - Bhatta, C. R. (Journal of the Institute of Engineering, 2011)
The central attraction of this paper is to prove holders inequality in some new spaces such as Grand Lebesgue Space LP). Small Lebesgue space LP)' and Banach Lattice space XP. Key words: Holders Inequality DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5119 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 259-262 Uploaded Date: 20 July, 2011